Grouping of Japan’s Media Sphere Elements - Sergeevich Lukin, Stanislav; Stepanovich Puiy, Anatoli; Borisovich Nikonov, Sergey; Vitalievna Baichick, Anna; Michailovna Glinternik, Eleonora (International Journal of Engineering and Technology, 2018)
Today, Japan's media sphere is undergoing significant changes under the influence of globalization and the development of information and communication technologies, but it retains traditional features. In these conditions, a comprehensive analysis of the modern Japanese media sphere, in particular, an analysis of the problems of its institutionalization, as well as the identification of the features of the functioning mechanism, allowing it to occupy the leading positions in the world in terms of the development of media institutions, is becoming relevant. This paper presents the results of research on the media sphere in Japan and suggests the grouping of its elements. The adoption of the proposed grouping of elements of the media sphere will help researchers understand the essence of the media system in Japan.Â Â Â